2013
DOI: 10.7754/clin.lab.2012.120810
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CC Chemokines CCL2, CCL5, and CCL11 is Associated with Duration of Disease and Complications in Type-1 Diabetes: A Study on Iranian Diabetic Patients

Abstract: Background: Type-1 diabetes (T1D) is defined as a heterogeneous autoimmune disease. Immune system related factors are important in the pathogenesis of T1D. Chemokines are important factors in the pathogenesis of several autoimmune diseases, including T1D. They are potent chemotactic cytokines with various functions such as maturation, trafficking of leukocytes, angiogenesis, and homing of stem cells. Therefore, the current study was aimed to examine whether expression of CC chemokines CCL2, CCL5, and CXCL11 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
(38 reference statements)
3
20
0
Order By: Relevance
“…Ncf1 m1J splenocytes displayed enhanced synthesis of proinflammatory chemokines implicated in T1D pathogenesis, including CCL5 (chemokine [C-C] motif ligand 5) (3- and 2.0-fold) and CXCL10 (chemokine [C-X-C motif] ligand 10) (332- and 2.0-fold) upon incubation with dispersed islet cells or mimotope, respectively ( Fig. 3 G – H ) ( 29 31 ). In addition to splenocytes, purified BDC-2.5.…”
Section: Resultsmentioning
confidence: 99%
“…Ncf1 m1J splenocytes displayed enhanced synthesis of proinflammatory chemokines implicated in T1D pathogenesis, including CCL5 (chemokine [C-C] motif ligand 5) (3- and 2.0-fold) and CXCL10 (chemokine [C-X-C motif] ligand 10) (332- and 2.0-fold) upon incubation with dispersed islet cells or mimotope, respectively ( Fig. 3 G – H ) ( 29 31 ). In addition to splenocytes, purified BDC-2.5.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has also been reported that CXCL12 and its relevant receptors (CXCR4 and CXCR7) in addition to serving as a particular actor in phenomenon of neovascularization (formation of new blood vesicles play paramount roles in regulation of hematopoietic cell trafficking and homing of bone marrow precursors within the bone marrow niches [24,25]. As stated earlier, CXCL1 and CXCL12 are both functionally angiogenesis and aid forming of new blood vessels while, CXCL9 and CXCL10 exhibit angiostasis properties and thus inhibit phenomenon of neovascularization and forming of new blood vessels [6,8,26]. A body of evidences have addressed the involvement of some other CXC chemokines in pathogenesis of GDM [27][28][29], however, the role of CXCL1, CXCL9, CXCL10 and CXCL12 in GDM pathogenesis yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there were a series of RANTES polymorphisms been reported, including -403A/G, -28C/ G, intronic variant INT1.1T/C and 524T/C [11][12][13][14][17][18][19][20]. They were involved in viral and non-viral diseases, such as AIDS, tuberculosis, type-1 diabetes, coronary artery disease, systemic lupus [33][34][35][36][37]. Different RANTES polymorphisms have different effects on the risk of HBV infection.…”
Section: Discussionmentioning
confidence: 99%